Suicide prevention-related Google searches and subsequent emergency department visits in California and Arizona, 2007-2015 - Hilary L. Colbeth; Sidra Goldman-Mellor; Ellen A. Eisen; Krista Neumann; Ralph Catalano; Corinne A. Riddell (Elsevier, 2024)
Introduction: United States emergency departments (ED) visit rates for nonfatal self-harm increased by 42% from 2001 to 2016. Previous suicide mortality research has provided conflicting evidence on the use of suicide-related Internet searches as a surveillance tool for self-harm and suicidal ideation. However, few have used rigorous approaches to account for autocorrelation at the aggregate level, and none have focused on Internet searches related to suicide prevention. Methods and results: Over a 9-year study period (2007-2015), suicidality-related search data were extracted using the Google Health Application Programming Interface (API) for Arizona and California - states, chosen for their differing age distributions and rigorous ED injury coding policies. We examined several combined suicide prevention-related search queries. Using autoregressive integration moving average (ARIMA) models and a Box-Jenkins approach, we assessed whether increased prevention-related Internet searches related to suicidality are predictive of lower subsequent ED visits related to suicidal ideation with or without self-harm injury. In both states, greater prevention-related queries were associated with lower ED visits approximately four to six weeks later. Conclusions: Our results indicate that Internet-based search volumes related to suicide prevention may have the potential to monitor suicidality and online suicide prevention resources offer meaningful opportunities for mental health support.